ARRB2 (β-Arrestin-2) Deficiency Alters Fluid Homeostasis and Blood Pressure Regulation. Issue 11 (23rd August 2022) - Mathieu, Natalia M.; Nakagawa, Pablo; Grobe, Connie C.; Reho, John J.; Brozoski, Daniel T.; Lu, Ko-Ting; Wackman, Kelsey K.; Ritter, McKenzie L.; Segar, Jeffrey L.; Grobe, Justin L.; Sigmund, Curt D.
Abstract : Background: GPCRs (G protein–coupled receptors) are implicated in blood pressure (BP) and fluid intake regulation. There is a developing concept that these effects are mediated by both canonical G protein signaling and noncanonical β-arrestin mediated signaling, but the contributions of each remain largely unexplored. Here, we hypothesized that β-arrestin contributes to fluid homeostasis and blood pressure (BP) regulation in deoxycorticosterone acetate (DOCA) salt hypertension, a prototypical model of salt-sensitive hypertension. Methods: Global β-arrestin1 ( Arrb1 ) and β-arrestin2 ( Arrb2 ) knockout mice were employed to evaluate drinking behavior, and BP was evaluated in Arrb2 -knockout mice. Age- and sex-matched C57BL/6 mice served as controls. We measured intake of water and different sodium chloride solutions and BP employing a 2-bottle choice paradigm with and without DOCA. Results: Without DOCA (baseline), Arrb2 -knockout mice exhibited a significant elevation in saline intake with no change in water intake. With DOCA treatment, Arrb2 -knockout mice exhibited a significant increase in both saline and water intake. Although Arrb2 -knockout mice exhibited hypernatremia at baseline conditions, we did not find significant changes in total body sodium stores or sodium palatability. In a separate cohort, BP was measured via telemetry in Arrb2 -knockout and C57BL/6 mice with and without DOCA. Arrb2 -knockout did not exhibit significant differences in BP before DOCA treatment when provided water alone, or when provided a choice of water and saline. However, Arrb2 -knockout exhibited an increased pressor response to DOCA-salt. Conclusions: These findings suggest that in salt-sensitive hypertension, ARRB2, but not ARRB1 (β-arrestin 1), might counterbalance the canonical signaling of GPCRs.